Alguns resultados de instabilidade linear para modelos de evolução não-lineares - Renan Henrique Martins (2018)
The main goal of this work is to study two methods of linear instability for evolution models which can be reduced as abstract Hamiltonian equations. To do so, we can rewrite the equation as an eigenvalue problem and the main focus consists in finding nonzero solutions (eigenfunctions) for this problem whose correspondent eigenvalue has positive real part. Our approach allows us to study the transversal linear instability to the generalized Kadomtsev-Petviashvili equation of I kind and the linear instability of solitary traveling wave solutions for the generalized Korteweg-de Vries equation